A fruit fly-based approach to unraveling enteropathy-causing pharmaceuticals - Pratama, Muhammad R.; Wahyudin, Elly; Putri, Tenri ZAD.; Hardiyanti, Widya; Fatiah, Dewita; Chaeratunnisa, Rizkya; Bapulo, Nurdewi N.; Latada, Nadila P.; Mudjahid, Mukarram; Nainu, Firzan (Narra J, 2024)
Enteropathy is a gastrointestinal disorder characterized by inflammation in the small intestine and one of the causes of enteropathy is the side effects of certain drugs, such as non-steroidal anti-inflammatory drugs (NSAIDs). The mechanism of NSAIDs, such as indomethacin, could inhibit prostaglandin synthesis, leading to a decrease in mucus production and small intestine integrity. To test the effects of a drug, it is necessary to undergo preclinical testing using animal models. Commonly used animal models such as mice and rats have several drawbacks including high cost, ethical issues, and long lifespan. Therefore, alternatives such as using invertebrate animals like Drosophila melanogaster as a more economical in vivo platform with genetic similarity to mammals and devoid of ethical concerns are needed. The aim of this study was to evaluate Drosophila melanogaster as an in vivo model organism in testing the side effects of pharmaceuticals that cause enteropathy. In this study, flies aged 3–5 days were starved and then placed into treatment vials comprising untreated control and indomethacin-treated (3.75 mM, 7.5 mM, and 15 mM). Survival analysis was conducted during the treatment period, followed by a Smurf assay test after seven days of treatment. Subsequently, the expression of pro-inflammatory cytokine-related genes (drs and totA), mitochondria stability-related genes (tom40), and endogenous antioxidant-related genes (sod1, sod2, and cat) was performed using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Our data indicated that indomethacin did not impact lifespan or cause intestinal damage. However, we observed increased expression of pro-inflammatory cytokine-related genes, including drs, and a twofold increase in totA gene expression. Furthermore, there was a significant upregulation of mitochondrial stability gene tom40, endogenous antioxidant genes sod1 and cat, and a threefold increase in sod2 at 15 mM indomethacin. Although no phenotypical changes in gut integrity were detected, the increased expression of pro-inflammatory cytokine genes suggests the occurrence of inflammation in the indomethacin-treated flies.